The Rowman and Littlefield Handbook on Workplace Diversity and Stratification - Melaku, Tsedale M.; Beeman, Angie; Winkler, Christoph (Rowman & Littlefield Publishers, 2023)
Organizations and institutions use diversity and inclusion mantras to signal opportunity and access for all. However, the real-world results are often underwhelming, and people are demanding that organizations recognize the value that diversity brings to a workplace and be held accountable to the diversity and inclusion mission statements on their websites. The Rowman & Littlefield Handbook on Workplace Diversity and Stratification provides a comprehensive yet concise overview of important issues, themes, and research regarding workplace diversity and stratification. The book analyzes present day and future implications of diversity in the workplace and offers concrete ways of developing policies and practices that will make diversity an intrinsic part of any organizational culture. Taking an interdisciplinary approach, the book covers topics including racism, sexism, socio-economic status, LGBTQ+ workers, education, intersectionality, neurodiversity, religion, and allyship. Practical, contemporary, and relevant, this is an excellent resource for anyone interested in understanding what workplace diversity and stratification mean for everyday people, institutions, and society as a whole.